Prototype Design of Client Server-Based Software to Control Client Computer in Computer Laboratories - Hernawati, Elis; Gunawan, Tedi; Hermansyah Suryadi, Aris (International Journal of Engineering and Technology, 2019)
In the practicum activities in the laboratories of School of Applied Science, Telkom University, the computer server is used by lecturers and the client computers are used by the students. When lecturers are teaching, the students often do not pay attention to the lecturers. The students operate the computers to play game, to access Facebook, or to do other activities that have nothing to do with the learning process. This paper describes the process of prototype design of client server-based software to control the client computers on the Local Area Network in the computer laboratory, so that the lecturers can control the activities of client computers used by the students. This software is designed to control the mouse, keyboard, and monitor screen of the client computers from the computer server. The method used to build the prototype of this software is the prototyping model. Meanwhile, the programming language used is Visual Basic. The results of this study are used to help programmers in building software to control clients in the computer laboratories, so that the software can help lecturers in the laboratory in monitoring the client computer used by students.Â